Assessment of Aquifer Susceptibility Due to Excessive Groundwater Abstraction; A Case Study of Yogyakarta-Sleman Groundwater Basin - Putra, Doni Prakasa Eka (2014)
Yogr-akarta-sleman groundwater basin is onc of productile groundu'ater basins in Indonesia The gro_undrvater basin is bLrilt by unconfineci sand_a<1ui1'er sysiem. Shce lhe early 1930's many schools' inilersiries and hotels have been developed i11 this arca to suppof education and tourjqn A'rivilics anrl since the beginning of 2000 s the numbcr ol buildings has jncreascd signjficar1lly' The cievelopment has rJsulteJin a rapid rate of land use and population changes \\'ith- the conseqtencc oi increasing groundvater pumping. |,'leasurement rcsuhs show tha! the rate of groundlvatcr table degraciati-oicxcee<ls 0.5 m/l'ear al some districts underlain by thc Aoundwaler basin Recause oflhis .oiditior,. it is necessary to assess the sus.epiib;1iry ol the aquifer io negarive impacts due 1() rhe excessive groundwatel punrping- The assessminr was conducted by overlying facio$ such as aquifer response c_haracteristics, "quifei sto.age .t,".acteristics, thickness ofthe aquifer' depth to groundwater tahic :nt1 rlistance liom ihe sca. The assess,rcnt results shorv that the excessile ground$aler abstraction to tle aquifer has caused noderatc to high sLrsceptibiiity lt mcans rhat the groundtrater pu:nping activities o; this groundwater basin should be r,anagcd and conirolled'